(untitled) (Damascus University Journal for engineering sciences, 2021)
This paper proposes a low complexity detection algorithm for M-PSK (M-ary Phase Shift Keying) in spatial modulation (SM) systems. Mathematically, we analyzed the formula for the maximum likelihood (ML). The mathematical analysis result was employed with features M-PSK constellation diagram to estimate values of the transmitted symbols. Simulation results showed that the proposed algorithm has the same performance (BER) as the ML- detector and significant reduces computational complexity. The results of the Low-Complexity (LC) algorithm is presented and validated by simulations with MATLAB.